Histories of the Internet and Political Communication in Lusophone Africa - Salgado, Susana (2017)
Politics, Policy, Populism and Online Media: Investigating Possible (Dis)Connections and Actors in Modern Democracies. (reference IF/01451/2014/CP1239/CT0004)